2005
DOI: 10.1128/aac.49.4.1279-1288.2005
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation and Oriented Transport of Ampicillin in Caco-2 Cells from Its Pivaloyloxymethylester Prodrug, Pivampicillin

Abstract: Pivampicillin (PIVA), an acyloxymethylester of ampicillin, is thought to enhance the oral bioavailability of ampicillin because of its greater lipophilicity compared to that of ampicillin. The fate of PIVA in intestinal cells and the exact location of its conversion into ampicillin have, however, never been unambiguously established. Polarized Caco-2 cells have been used to examine the handling of PIVA and the release of ampicillin from PIVA by the intestinal epithelium. Experiments were limited to 3 h. Cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 50 publications
1
10
0
Order By: Relevance
“…Also, these data should be interpreted with caution, because CDP323 might have been partially hydrolyzed during the assay. Indeed, hydrolytic enzymes can be released from Caco-2 brush border membranes, as reported elsewhere (Chanteux et al, 2005;Brouwers et al, 2007;Yuan et al, 2009).…”
Section: Downloaded Frommentioning
confidence: 94%
“…Also, these data should be interpreted with caution, because CDP323 might have been partially hydrolyzed during the assay. Indeed, hydrolytic enzymes can be released from Caco-2 brush border membranes, as reported elsewhere (Chanteux et al, 2005;Brouwers et al, 2007;Yuan et al, 2009).…”
Section: Downloaded Frommentioning
confidence: 94%
“…Therefore the absorption mechanisms of these ampicillin prodrugs have not been fully investigated until now. Recently, Chanteux et al 18) reported that pivampicillin, which was added to the apical side of Caco-2 cells, was efficiently hydrolyzed to ampicillin inside the cells and that the ampicillin was preferentially released to the basolateral medium via an MRP-like transporter. The aim of this study was to assess how Caco-2 cells deal with bacampicillin as compared with pivampicillin.…”
Section: Discussionmentioning
confidence: 99%
“…It was also thought that pivampicillin was easily converted to ampicillin in the Caco-2 cells, which is consistent with results presented in recent papers. 18,19) Because an Eadie-Hofstee plot (Fig. 2) implied possible involvement of a specialized transport system for bacampicillin, the changes in its uptake were investigated in the presence of various organic cations.…”
Section: Discussionmentioning
confidence: 99%
“…ucl.ac.uk/nomenclalure/genefamily/abc.html). In polarized cells, MRPs localize to either the basolateral membrane (which may increase drug absorption) [6,7] or apical membrane (which enhance drug elimination). In non-polarized cells, such as transporters, MRPs pump intracellular drugs out, resulting in a decrease in drug concentration.…”
Section: Introductionmentioning
confidence: 99%
“…This inhibits the progression of the enzyme topoisomerase II, which relaxes supercoils in DNA leading to transcription. [6,16] A series of cancer cell lines have been used to study doxorubicin resistance. However, there is no data regarding osteosarcoma cells.…”
Section: Introductionmentioning
confidence: 99%